2004
DOI: 10.1103/physrevlett.93.097004
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Nanoscale Electronic Inhomogeneity in the Lightly Doped Mott InsulatorCa2xNax

Abstract: The spatial variation of electronic states was imaged in the lightly doped Mott insulator Ca2−xNaxCuO2Cl2 using scanning tunneling microscopy / spectroscopy (STM/STS). We observed nano-scale domains with a high local density of states within an insulating background. The observed domains have a characteristic length scale of 2 nm (∼4-5a, a : lattice constant) with preferred orientations along the tetragonal [100] direction. We argue that such spatially inhomogeneous electronic states are inherent to slightly d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
69
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 24 publications
14
69
0
Order By: Relevance
“…However, the absence of a dip in the polarization function at the lowest times indicates the presence of a large number of low field sites -superconducting and magnetic regions intercalated on a microscopic (≤ 2 nm) scale [8,9,14,21]. These observations suggest the presence of magnetic stripes/droplets, in agreement with independent indications [4,8,9,10,11,13,14,21] from transport and spectroscopic studies for the nonsuperconducting dopings. From these studies we may conclude that superconductivity coexists with glassiness on a microscopic scale throughout the bulk of the material.…”
supporting
confidence: 81%
“…However, the absence of a dip in the polarization function at the lowest times indicates the presence of a large number of low field sites -superconducting and magnetic regions intercalated on a microscopic (≤ 2 nm) scale [8,9,14,21]. These observations suggest the presence of magnetic stripes/droplets, in agreement with independent indications [4,8,9,10,11,13,14,21] from transport and spectroscopic studies for the nonsuperconducting dopings. From these studies we may conclude that superconductivity coexists with glassiness on a microscopic scale throughout the bulk of the material.…”
supporting
confidence: 81%
“…1. The presented CVC pattern for this highly symmetric junction undoubtedly demonstrates the availability of a nonsymmetric contribution of unknown nature and magnitude, although the non-symmetricity is much less than in the case of truly nonsymmetric junctions [2,7,18,23,26]. One can see well-developed dip-hump structures beyond the coherent superconducting peaks.…”
Section: Experimental Partmentioning
confidence: 85%
“…Since we assume a symmetric junction, the calculated superconducting coherent peaks in all demonstrated figures turned out equal by height. Different experimental peak heights may be due to the experimental uncertainties and the differentiation of raw data, J V ( ), the latter being already averaged over various patches of the cuprate surface [17,26]. Of course, such a disparity varies from measurement to measurement at random.…”
mentioning
confidence: 99%
“…1,8,9 STS has revealed that the cuprates have a spatially inhomogeneous electronic structure, including modulations in the LDOS and superconducting gap magnitude. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the d-wave superconducting phase, the LDOS modulations can arise from quasiparticle interference (QPI), due to the scattering of wave-like quasiparticles off impurities. 12,15,22,[25][26][27] The wavevectors of the modulations can be determined from the Fourier transform of the LDOS.…”
Section: Introductionmentioning
confidence: 99%